PERSEPSI KONSUMEN TOKO ONLINE PONTIANAK KERUPUK BASAH TERHADAP LAYANAN GRATIS ONGKOS KIRIM - Ulandari, Ulandari; Basri, Muhammad; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
At the moment people prefer to shop online because the purchasing decision process is more practical. The fact is that online purchases can save time, costs, and convenience when making purchases without going to the intended store, as well as increasing competition for sellers' products or services so consumers must act fraudulently in making decisions to buy. This is due to consumer perceptions before deciding to buy approduct. The technique utilized was a quantitative strategy utilizing a populace of 128 people more than 2 years. Data collection techniques by questionnaire and desk study. In this study, data is analyzed using simple linear regression. The resultssshow consumer perception of Pontianak Kerupuk Basah online shop for free shipping services were classified as very high, namely 85.08%. This is based on the calculation of consumer buying decision indicators (awareness of problems, gathering information, weighing options, making purchasing decisions, and following through on purchases).